Diseño e implementación de un centro de interpretación cultural para la carrera de ecoturismo en la facultad ciencias ambientales de la Universidad Técnica Estatal de Quevedo - Moncayo Solís, Idita Jessenia (2013)
The present research work was carried out at the Faculty of environmental sciences, property of the UTEQ, located Av. Quito, k 1 ½ vía Santo Domingo de los Tsáchilas; Cantón Quevedo, Los Ríos province. Located at the geographic coordinates of 79 ° 28' 30 "West longitude and 1 ° 20' 30" South latitude, at an average temperature of 24° C, the annual precipitation is between approximately 2000 to 3000 mm and is considered a tropical humid forest (Bh-T). The main objective was to implement a Cultural Centre for the career of ecotourism, and this was carried out by a market research which allowed us to learn the subject matter of the (CIC) and interpretation center "Las Tolas" Cultural contribution that will provide students with State Technical University of Quevedo, about the knowledge of cultures or the services provided by the cultural interpretation center. You were collecting information of cultural resources and the process of education towards the conservation of the environment. Also discussed, the means of distribution for the realization of this CIC, there will be an area of 5.89 cm x 8.94 cm, which fragmented into three rooms with elaborate Board rafting divisions; the reception room has a size of 4.89 cm x 1.80 cm; the showroom will measure 3.44 cm x 6m; and the audiovisual room measure 5.30 x 2.45cm. The elaboration of the CIC and distribution media design used the following materials; varnish, cane bamboo, wood laurel, balsa, stickers, posters, models, archaeological pieces, fence, paint, brush, nails, cutting of wood, polishing, sanding, cabuya etc Is concludes that Cultural "Las Tolas" (CIC) Centre is to increase sensitivity in the persons of a creative learning that allows awareness to conservation and rescue of our cultures. And it is recommended to involve students of ecotourism to make bonding or professional practice.